Binary Sudoku as a game in technical high school: an experience report - Campano Junior, Maurilio Martins; Santini, Larissa Fátima de Souza da Luz; Track, Mateus Bonfim; Assumpção, Marcos de; Aylon, Linnyer Beatrys Ruiz (Companion Proceedings of the Brazilian Symposium on Computer Games and Digital Entertainment (SBGames); 2023: Companion Proceedings of the 22nd Brazilian Symposium on Games and Digital Entertainment, 2023)
Educational games facilitate learning by allowing playfulness and fun in a learning environment. Simple examples such as Sudoku or Binary Sudoku promote logical challenges when played and can be adapted to different difficulty levels and age groups. Therefore, the objective of this study is to evaluate the application of Binary Sudoku in the classroom, aiming to integrate and contextualize students with the binary representation system. The practice was conducted in three public schools, involving a total of 144 students from technical high school. The results indicate that this activity is both challenging and enjoyable, and it can stimulate student learning.